EVALUATION OF THE IMPACT OF HEALTH EDUCATION ON THE KNOWLEDGE AND ATTITUDES OF OLDER ADULTS IN HYPERTENSION MANAGEMENT IN MOJOKERTO REGENCY - Hasan Nidlom (International Journal of Social Science, 2025)
Limited knowledge and attitudes among older adults regarding hypertension represent a significant public health issue in Mojokerto Regency, affecting medication adherence, dietary habits, and physical activity. This study aimed to evaluate the effect of health education on older adults’ knowledge and attitudes in hypertension control. A qualitative case study approach was employed, collecting data through in-depth interviews with health workers, older adults, and elder cadres, as well as observations and documentation of educational activities. Data analysis followed Miles and Huberman’s techniques, including data reduction, presentation, and verification. Findings indicated that health education effectively increased older adults’ knowledge; however, behavioral and attitudinal changes require additional support. These results provide both theoretical and practical contributions for developing more effective health education programs for older adults